Research Progress on the Animal Models of Drug-Induced Liver Injury: Current Status and Further Perspectives - Pan, Yingying (Biomed Res Int, 2019)
Drug-induced liver injury (DILI) is a major concern in clinical studies as well as in postmarketing surveillance. It is necessary to establish an animal model of DILI for thorough investigation of mechanisms of DILI and searching for protective medications. This article reviews the current status and future perspective on establishment of DILI models based on different hepatotoxic drugs, as well as the underlying mechanisms of liver function damage induced by specific medicine. Therefore, information from this article can help researchers make a suitable selection of animal models for further study.